Molecular Typing and Epidemiological Study of Salmonella enterica Serotype Typhimurium Isolates from Cattle by Fluorescent Amplified-Fragment Length Polymorphism Fingerprinting and Pulsed-Field Gel Electrophoresis - Tamada, Yukihiro (American Society for Microbiology, 2001)
One hundred twenty Salmonella enterica serotype Typhimurium strains, including 103 isolates from cattle gathered between 1977 and 1999 in the prefecture located on the northern-most island of Japan, were analyzed by using fluorescent amplified-fragment length polymorphism (FAFLP) and pulsed-field gel electrophoresis (PFGE) to examine the genotypic basis of the epidemic. Among these strains, there were 17 FAFLP profiles that formed four distinct clusters (A, B, C, and D). Isolates that belonged to cluster A have become increasingly common since 1992 with the increase of bovine salmonellosis caused by serotype Typhimurium. PFGE resolved 25 banding patterns that formed three distinct clusters (I, II, and III). All the isolates that belonged to FAFLP cluster A, in which all the strains of definitive phage type 104 examined were included, were grouped into PFGE cluster I. Taken together, these results indicate that clonal exchange of serotype Typhimurium has taken place since 1992, and they show a remarkable degree of homogeneity at a molecular level among contemporary isolates from cattle in this region. Moreover, we have sequenced two kinds of FAFLP markers, 142-bp and 132-bp fragments, which were identified as a polymorphic marker of strains that belonged to clusters A and C, respectively. The sequence of the 142-bp fragment shows homology with a segment of P22 phage, and that of the 132-bp fragment shows homology with a segment of traG, which is an F plasmid conjugation gene. FAFLP is apparently as well suited for epidemiological typing of serotype Typhimurium as is PFGE, and FAFLP can provide a source of molecular markers useful for studies of genetic variation in natural populations of serotype Typhimurium.